Study of Creatinin Levels of Patients Receiving Antipsycotic Treatment at Mutiara Sukma Psychiatric Hospital, Nusa Tenggara Barat: Studi Kadar Kreatinin Pasien Jiwa yang Menerima Pengobatan Antipsikotik di Rumah Sakit Jiwa Mutiara Sukma, Nusa Tenggara Barat - Sukmana, Dhika Juliana; Mentari, Ika Nurfajri; Anjelin, Desak Putu (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Mental disorders are clinical and social problems that must be addressed immediately. Long-term use of the drug can cause damage to kidney function and worsen the work of the kidneys. Creatinine is a waste product of creatine phosphate metabolism that occurs in the muscles and is then released into the blood circulation, then transported to the kidneys. The purpose of this study was to determine how the creatinine levels of mental patients receiving antipsychotic treatment at Rumah Sakit Jiwa Mutiara Sukma Hospital, Nusa Tenggara Barat Province. The research method used is qualitative. The type of research used is descriptive, namely looking at data from the Clinical Pathology laboratory installation and medical records to determine the results of examination of creatinine levels in patients with mental disorders. The results showed that from data in the Clinical Pathology laboratory and medical records at Rumah Sakit Jiwa Mutiara Sukma, NTB Province from June-December 2020 with a total of 40 data, there were 30 patients (75%) who had normal creatinine levels, 2 patients (5%) had normal creatinine levels. creatinine levels were low, and 8 patients (20%) had high creatinine levels.